Jamaican foreign exchange market: lessons from the experience with a floating exchange rate regime and the abolition of exchange controls. - BENNETT, Karl M. (1994)
Outlines the institutional setting within which the foreign exchange market operated, and argues that this had a bearing on the formulation of expectations and market behaviour. Analyses the performance of the foreign exchange market since the return to the market based exchange rate regime, and assesses why the positive developments following the stabilization initiatives of April 1992 have not been sustained.